Febrile reaction after hematopoietic stem cell infusion is more frequent if no steroid premedicaton is given which results in more frequent use of antibiotics in early post-transplant phase : Febrilne reakcije nakon infuzije krvotvornih matičnih stanica češće su ukoliko se ne primijeni premedikacija kortikosteroidima što rezultira većom upotrebom antibiotika rano nakon transplantacije - Romić, Lucija (Array, 2021)
Background: There is no consensus as to the need for steroid premedication before fresh product hematopoietic stem cell (HSC) infusion. In case of febrile reaction post-HSC infusion, on-call staff frequently prescribe antibiotics empirically. Considering the recent data on the value of microbiota and its influence on GVHD incidence, we analysed the frequency of febrile reactions and the use of antibiotic after HSC infusion in 149 consecutive patients. Methods: In the time period between 1/2018 and 10/2019, 149 patients were subject to transplantation in our institution. Per institutional standard operating procedure (SOP), all the patients received premedication before hematopoietic stem cell infusion consisting of 20 mg chloropyramine-chlorid iv, and in case of ABO incompatible graft 1 mg/kg methylprednisolone iv. Retrospective data was collected by using patient charts. Survival probability was calculated by applying Kaplan-Meier method. Results: Fifty-two patients received steroids, 12 patients (23%) developing fever after graft infusion, 46 patients received no steroids, 26 of them (57%) developed fever (p<0.001). There was no difference in the number of patients having positive blood cultures. Nine (17%) and 16 (35%) patients received IV antibiotics in the “steroid” and no-steroid” group, respectively (p<0.05). There was no difference in survival between “steroid” and “no-steroid” group. Conclusions: Even with no difference in the frequency of febrile episodes caused by systemic infection, a significantly more patients not receiving steroid premedication develop fever and are treated with IV antibiotics, which could potentially have further implications on transplantation outcomes due to its influence on microbiota early post-transplant.